Kingdom of the Netherlands : Curacao and Saint Maarten: 2011 Article IV Consultation: Staff Report; Informational Annex; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The two newly autonomous countries within the Kingdom of the Netherlands face substantial challenges. Growth has been low, and unemployment high. The current account deficit has widened to worrisome levels, increasing the vulnerability of the peg to the U.S. dollar and stimulating calls for dollarizing or dissolving the currency union. A substantial adjustment is needed to bring the underlying current account deficit to historically sustainable levels over the medium term. This could be facilitated by measures to restrain credit growth, supported by fiscal consolidation.